Finishing shrink film

By using compounded multicomponent melt blend composition in the finishing shrink film, combining PCR resin material and original polymer resin material, the problem of insufficient physical characteristics of the film made of recycled materials is solved, and the improvement is achieved PCR resin load capacity and effect of retaining film properties.

CN119403873APending Publication Date: 2025-02-07DOW GLOBAL TECHNOLOGIES LLC
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202280096987.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2022-06-16
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In the prior art, finishing shrink films made of recycled materials are inferior in physical properties as well as products made of original materials, resulting in limitations in high-end transparent film applications and packaging applications.

Method used

To increase the total PCR of the blend formulation by blending using a compounded multicomponent melt blend composition, including combinations of two or more PCR resin materials and one or more original polymer resin materials The load capacity of the resin material while maintaining mechanical, thermal and optical properties.

Benefits of technology

It has achieved the improvement of the load of PCR resin material for finishing shrink films, while maintaining or improving the mechanical, thermal and optical properties of the films, and is suitable for high-end transparent films and packaging applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119403873A_ABST
    Figure CN119403873A_ABST
Patent Text Reader

Abstract

A shrink film comprising: at least one monolayer or multilayer film having at least one layer comprising a formulated resin wherein the formulated resin comprises: (a) at least one post-consumer recycled resin derived from recycled high density polyethylene resin having a density of from 0.940 g / cc to 0.970 g / cc and a melt index I2 of from 0.01 g / 10 min to 1.0 g / 10 min; (b) at least one post consumer recycled resin derived from recycled low density polyethylene resin having a density of from 0.915 g / cc to 0.935 g / cc and a melt index I2 of from 0.1 g / 10 min to 1.0 g / 10 min; and (c) at least one raw low density polyethylene resin having a density of from 0.915 g / cc to 0.925 g / cc and a melt index I2 of from 0.1 g / 10 min to 2 g / 10 min.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to packaging films; and more particularly, the present invention relates to collation shrink films made from polymer blend compositions including recycled plastic or post-consumer recycled (PCR) resin materials and the preparation of such collation shrink films. Background Art

[0002] It is believed that the use of recycled materials is better for the environment and reduces the waste of natural resources used for disposable products. Therefore, the more recycled materials that can be used, the better for the environment. However, it is generally believed in the art that the satisfaction of the physical properties of products made from recycled materials is generally not as good as products made from virgin materials. Therefore, due to the loss of physical properties of products made from recycled materials, the use of recycled materials in products is often limited. For example, when compared to virgin polyethylene (PE), PCR resin materials have inferior properties due to contamination and excessive thermal history associated with the recycling process of PCR resin materials, thereby limiting the maximum loading of PCR resin materials that can be achieved when blending PCR resin materials with other resins. Upgrading PCR resin materials for high-end transparent film applications is also a problem; and it is difficult to incorporate meaningful and appropriate amounts of PCR resin materials into blend formulations used to manufacture end-use products.

[0003] Examples of end uses requiring PCR resin materials include collation shrink film (CSF) packaging applications. Collation shrink films and methods of making collation shrink films are known. However, the use of PCR resin materials to make collation shrink films is limited due to the following reasons: (1) lack of uniformity of PCR resin materials; (2) high contamination of PCR resin materials, and (3) defects in the film caused by the use of PCR resin materials (e.g., undesirable gel formation; reduced processability; and degradation of the mechanical properties of the film). Therefore, it is necessary to find solutions to address the above limitations when using recycled products to produce films or other articles without affecting the quality of the film or the article made from the film. Specifically, it is desirable to produce collation shrink films containing a meaningful amount of PCR resin material, wherein the film containing the PCR resin material has a combination of good aesthetics (e.g., reduced defect count), toughness (e.g., puncture resistance, dart impact and tear strength), stiffness (e.g., secant modulus), shrinkage force, compaction force, shrinkage rate and processability. It is known that the above film properties are each improved. However, currently available film structures utilizing PCR resin materials fail to satisfactorily combine all of the above-mentioned properties in a film having a sufficiently thin gauge to be commercially attractive. Summary of the invention

[0004] One general embodiment of the present invention relates to a compounded multi-component melt blend composition or formulation (also referred to herein as a "formulated resin") comprising a combination of two or more PCR resin materials and one or more virgin polymer resin materials; wherein the formulated resin can be compounded into a single pellet form of material. The single pellet form of material can then be used to produce a collation shrink film (CSF) and the resulting CSF can be used in packaging applications.

[0005] For example, in a preferred embodiment, a melt blend formulation for forming a shrink film therefrom comprises:

[0006] (a) at least one post-consumer recycled resin derived from recycled high density polyethylene resin having a density of 0.940 g / cc to 0.970 g / cc and a melt index I2 of 0.01 g / 10 min to 1.0 g / 10 min;

[0007] (b) at least one post-consumer recycled resin derived from recycled low density polyethylene resin having a density from 0.915 g / cc to 0.935 g / cc and a melt index I2 from 0.1 g / 10 min to 2.0 g / 10 min;

[0008] (c) at least one pristine low density polyethylene resin having a density of 0.915 g / cc to 0.925 g / cc and a melt index I2 of 0.1 g / 10 min to 1 g / 10 min; and

[0009] (d) Optionally, if desired, at least one additive different from components (a), (b) and (c). wherein the loading of post-consumer recycled resin in the formulated resin is greater than or equal to 30% to 90%.

[0010] In another general embodiment, the present invention is directed to a pelletized article made from the compounded multi-component melt blend formulation described above.

[0011] In yet another general embodiment, the present invention is directed to a film article (e.g., CSF) made from the above-described granular article. For example, it has been found that CSF products made from the polymer blend formulations of the present invention comprising two or more PCR resin materials as discussed and described herein can have improved properties. In one embodiment, the present invention is directed to a multilayer CSF structure, wherein at least one layer of the CSF structure comprises a layer made from the above-described formulated resin and the granular article. In a preferred embodiment, the multilayer CSF film structure can be at least a three-layer structure comprising a core layer and two skin layers, wherein the skin layers comprise high optical skin layers, and wherein the core layer comprises the above-described formulated resin and the granular article.

[0012] In other general embodiments, the present invention is directed to methods of making the compounded multi-component melt blend formulations, pelletized articles, and CSF products described above.

[0013] An object of the present invention is to provide a compounded multi-component melt blend formulation, which includes a combination of two or more PCR resin materials and a virgin polymer material; and the formulation can be compounded into a material in a single pellet form. By blending two or more different grades of suitable PCR resin materials with one or more virgin polymer materials, the total PCR resin material loading level of the blend formulation can be increased while maintaining the mechanical, thermal and optical properties of the end-use product made from the compounded multi-component melt blend formulation. In addition, the processability of the material in a single pellet form can be improved; and the shrinkage force of the CSF can be increased for use in CSF applications. In addition, by incorporating a filtration step into the compounding process, the process can produce a single pellet compounded product that can be easily processed into a film product with extremely low gel content and high aesthetics.

[0014] Another object of the present invention is to provide a formulated resin for producing CSF; wherein the formulated resin used in the CSF comprises a combination of two or more PCR resin materials and one or more virgin polymer materials; and wherein one PCR resin material (e.g., one PCR resin material among the two or more PCR resin materials) is derived from recycled high-density polyethylene resin obtained from blow-molded bottles (e.g., milk bottles, beverage bottles, sauce bottles, etc.), and another PCR resin material (e.g., another PCR resin material among the two or more PCR resin materials) is derived from recycled flexible films made of polyethylene (e.g., shrink films, logistics films, stretch films, etc.).

[0015] Another object of the present invention is to provide a CSF that (1) is prepared from the above-described formulated resin having an increased percentage loading level of PCR resin material; (2) has a low number of defects; (3) exhibits good mechanical properties; and (4) exhibits good contractile force properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 is a graphical illustration showing the melt strength of various sample pellets prepared in the Examples. DETAILED DESCRIPTION

[0017] Reference will now be made in detail to embodiments of formulated resins, pellet articles, and films containing PCR materials. The formulated resins, pellet articles, and films may be used for finishing shrink film applications; however, it should be noted that these articles are merely exemplary illustrative implementations of the embodiments disclosed herein. The embodiments are applicable to other resin, pellet, film, or molded article technologies where the following properties are desired: incorporating PCR resin material; having a low number of defects; exhibiting good mechanical properties; and exhibiting good shrink properties.

[0018] The term "composition" refers to a mixture of materials comprising the composition, as well as reaction products and decomposition products formed from the materials of the composition.

[0019] As used herein, the term "polymer" refers to a polymeric compound prepared by polymerizing monomers of the same or different types. The general term "polymer" thus encompasses: (1) the term homopolymer (used to refer to polymers prepared by polymerizing only one type of monomer, it being understood that trace amounts of impurities may be incorporated into the polymer structure); and (2) the term copolymer or interpolymer (used to refer to polymers prepared by polymerizing two or more different monomers, it being understood that trace amounts of impurities may be incorporated into the polymer structure). Trace amounts of impurities (e.g., catalyst residues, chain transfer agents, branching agents, peroxide residues, etc.) may be incorporated into and / or within the polymer. The polymer may be a single polymer or a polymer blend.

[0020] "Interpolymer" refers to a polymer prepared by polymerizing at least two different types of monomers. Thus, the generic term interpolymer includes copolymers and other polymers prepared by polymerizing two or more different monomers (such as terpolymers).

[0021] Among other terms, "virgin polymer", "virgin material", "virgin base polymer", "virgin raw material", "virgin resin", "primary polymer" and "primary raw material" refer to polymers that can be characterized as "primary (original) raw materials", as defined in ISO 18604. Therefore, the general term virgin with respect to polymers or raw materials includes polymers or materials from initial sources that have never been processed into any form of end-use product. In other words, a virgin polymer or material is pure, unmodified, unmixed and unadulterated, i.e., the initial, raw material has not been mixed or admixed with any other substance or material. Virgin polymers are discussed further herein.

[0022] The "blend formulations" and "formulated resins" of the present invention include "virgin polyethylene resins", i.e., the virgin polymer material as described above, and include a polyethylene composition or a blend of multiple polyethylene compositions. Such blends of multiple polyethylene compositions may comprise multimodal reactor blends or physical blends of multiple polyethylenes melt blended, dry blended, etc.

[0023] The terms "pre-consumer recycled polymers" and "post-industrial recycled polymers" refer to polymers comprising a blend of polymers recovered from pre-consumer materials as defined by ISO 14021. Thus, the generic term pre-consumer recycled polymers includes blends of polymers recovered from materials diverted from waste streams during the manufacturing process. The generic term pre-consumer recycled polymers does not include the reuse of materials that are generated in a process and can be recovered in the same process in which they were generated, such as reprocessing, regrind, or scrap.

[0024] As used herein, the term "post-consumer recycled" (or "PCR") polymer refers to a polymer material that includes materials that were previously used in consumer or industrial applications (i.e., pre-consumer recycled polymers and post-industrial recycled polymers). PCR resin materials are typically collected from recycling programs and recycling plants. PCR resin materials may include one or more of polyethylene, polypropylene, polyester, poly(vinyl chloride), polystyrene, acrylonitrile butadiene styrene, polyamide, ethylene vinyl alcohol, ethylene vinyl acetate, or polyvinyl chloride. PCR resin materials may include one or more contaminants. Contaminants may be the result of the use of polymeric materials before being reused. For example, contaminants may include paper, ink, food scraps, or other recycled materials other than polymers that may result from a recycling process. PCR resin materials are different from virgin polymer materials. Virgin polymer materials (such as virgin bimodal polyethylene resins) do not include materials that were previously used in consumer or industrial applications. After the initial polymer manufacturing process, the virgin polymer material has not yet undergone or has not otherwise undergone a heating process or a molding process. The physical, chemical, and flow properties of PCR resin materials are different compared to virgin polymer resins, which in turn may present challenges for incorporating PCR resin materials into commercial use formulations.

[0025] As defined in ISO 14021:2016, "PCR polymer", "PCR resin", "PCR material" or "PCR resin material" is also used herein. The above terms refer to polymers or materials recycled from post-consumer materials, including blends of polymers or materials, as defined in ISO 14021. The general term PCR polymer, resin or material includes blends of polymers / materials recycled from materials generated by households or by commercial, industrial and institutional facilities in the role of such facilities as end users of the product that can no longer be used for the intended purpose of the product. The general term PCR polymer / material also includes blends of polymers / materials recycled from return materials from the distribution chain. Some characteristic features of PCR polymers / materials typically include, for example, a melt index in the range of 0.01 g / 10min to 5 g / 10min; a density of 0.910 g / cc to 0.965 g / cc; and an I of 5 to 20. 10Typically, PCR polymers / materials are usually blends of various polyethylene resins.

[0026] The term "recycled polyethylene" refers to polymers (eg, polyethylene) recovered from post-consumer materials as defined in ISO 14021, polymers recovered from pre-consumer materials as defined in ISO 14021, and combinations thereof.

[0027] The term "PCR resin formulation" refers to a polymer "blend formulation" or "formulated resin" as described above; and comprises at least one PCR resin, at least one ethylene / α-olefin copolymer, at least one virgin polymer material, at least one high-density polyethylene, and optionally other components and additives. In many embodiments discussed herein below, the PCR resin formulation can be its own product (e.g., in pellet form) or can be further blended with other materials to produce another product, such as a film, sheet, etc.

[0028] The terms "polyolefin", "polyolefin polymer" and "polyolefin resin" refer to polyolefins prepared by reacting simple olefins (also known as olefins) with the general formula C n H 2n Thus, the generic term polyolefin includes polymers prepared by polymerizing ethylene monomers with or without one or more comonomers (such as polyethylene) and polymers prepared by polymerizing propylene monomers with or without one or more comonomers (such as polypropylene).

[0029] The terms "polyethylene (PE)" and "ethylene-based polymers" refer to polyolefins containing greater than 50 mole percent (%) of ethylene monomer-derived units, including polyethylene homopolymers and polyethylene copolymers (referring to units derived from two or more comonomers). Common forms of ethylene-based polymers (e.g., polyethylene) known in the art include, but are not limited to: low-density polyethylene (LDPE); linear low-density polyethylene (LLDPE); ultra-low-density polyethylene (ULDPE); very low-density polyethylene (VLDPE); single-site catalyzed linear low-density polyethylene, including both linear low-density resins and substantially linear low-density resins (m-LLDPE); medium-density polyethylene (MDPE); and high-density polyethylene (HDPE).

[0030] The term "LDPE" or "low density polyethylene" may also be referred to as "high pressure ethylene polymer" or "highly branched polyethylene"; and refers to an ethylene homopolymer prepared using free radical, high pressure (e.g., greater than or equal to 100 MPa, such as 100 MPa to 400 MPa) polymerization. For example, the polymer is partially or completely homopolymerized or copolymerized in an autoclave or tubular reactor using a free radical initiator such as a peroxide (see, e.g., U.S. Pat. No. 4,599,392). LDPE resins typically have a density in the range of 0.916 g / cc to 0.935 g / cc.

[0031] The term "LLDPE" or "linear low density polyethylene" includes resins made using a Ziegler-Natta catalyst system and resins made using single-site catalysts, including but not limited to dimetallocene catalysts (sometimes referred to as "m-LLDPE"), phosphinimines, and constrained geometry catalysts; and resins made using post-metallocene, molecular catalysts, including but not limited to bis(biphenylphenoxy) catalysts (also known as polyvalent aryloxyether catalysts). LLDPE includes linear, substantially linear, or heterogeneous ethylene (i.e., polyethylene) based copolymers or homopolymers. LLDPE contains less long chain branching than LDPE, and includes substantially linear ethylene polymers (which are further defined in U.S. Pat. No. 5,272,236, U.S. Pat. No. 5,278,272, U.S. Pat. No. 5,582,923, and U.S. Pat. No. 5,733,155), homogeneously branched linear ethylene polymer compositions (such as those in U.S. Pat. No. 3,645,992), heterogeneously branched ethylene polymers (such as those prepared according to the process disclosed in U.S. Pat. No. 4,076,698), and / or blends thereof (such as those disclosed in U.S. Pat. No. 3,914,342 or U.S. Pat. No. 5,854,045). LLDPE resins can be prepared via gas phase, solution phase, or slurry polymerization, or any combination thereof, using any type of reactor or reactor configuration known in the art.

[0032] The term "MDPE" refers to polyethylene having a density of 0.926 g / cc to 0.945 g / cc. "MDPE" is typically prepared using chromium or Ziegler-Natta catalysts or using single site catalysts including but not limited to dual metallocene catalysts and constrained geometry catalysts.

[0033] The term "HDPE" or "high density polyethylene" refers to an ethylene-based polymer (i.e., polyethylene) having a density greater than 0.940 g / cc, typically prepared with a Ziegler-Natta catalyst, a chromium catalyst, or a single-site catalyst (including but not limited to dual metallocene catalysts and constrained geometry catalysts). For greater clarity, while HDPE is an ethylene / α-olefin copolymer, it is not a lower density ethylene / α-olefin copolymer having a density of 0.850 g / cc to 0.910 g / cc as described herein.

[0034] As used herein, the terms "comprising," "including," "having," and derivatives thereof are not intended to exclude the presence of any additional components, steps, or procedures, whether or not specifically disclosed. For the avoidance of any doubt, all compositions claimed through use of the term "comprising" may include any additional additives, adjuvants, or compounds, whether polymeric or otherwise, unless stated to the contrary. In contrast, the term "consisting essentially of excludes from the scope of any subsequently recited any other components, steps, or procedures, except those that are not essential to operability. The term "consisting of excludes any ingredient, step, or procedure not specifically recited or listed.

[0035] As used throughout this specification, the abbreviations given below have the following meanings, unless the context clearly indicates otherwise: "=" means "equal to"; "@" means "at"; "<" means "less than"; ">" means "greater than"; "≤" means "less than or equal to"; "≥" means "greater than or equal to"; "I2" means "melt index"; g = gram; mg = milligram; pts = parts by weight; kg = kilogram; kg / h = kilogram per hour; Kg / s = kilogram per second; g / cc = gram per cubic centimeter; kg / m 3 = kilogram per cubic meter; g / mol = gram per mole; L = liter; mL = milliliter; g / L = gram per liter; Mw = mass molecular weight; Mn = number molecular weight; Mz = z-average molecular weight; m = meter; μm = micrometer; mm = millimeter; cm = centimeter; cm 3 = cubic centimeter; min = minute; s = second; mm / s2 = millimeter per square second; mm / s = millimeter per second; ms = millisecond; hr = hour; mm / min = millimeter per minute; m / s = meter per second; ℃ = degrees Celsius; C / min = degrees Celsius per minute; mPa.s = millipascal-second; mPa = megapascal; MPa = megapascal; kPa = kilopascal; Pa.s / m 2 = Pascal-second per square meter; N = Newton; cN = hundredth of a Newton; mN = millinewton; gf = gram-force; rpm = revolutions per minute; mm 2= square millimeters; g / 10min = grams per 10 minutes; J = joule; J / g = joule per gram; % = percent; eq% = equivalent percent; vol% = volume percent; and wt% = weight percent.

[0036] Unless otherwise indicated, all percentages, parts, ratios and similar amounts are defined by weight. For example, unless otherwise indicated, all percentages described herein are weight percentages (wt %).

[0037] Unless otherwise specified, temperatures are expressed in degrees Celsius (°C), and "ambient temperature" means between 20°C and 25°C.

[0038] In a broad embodiment, the present invention is directed to a polymer blend formulation or composition for use in producing a film product and more particularly a collation shrink film (CSF) product. Generally, the present invention includes formulated resins useful for preparing films, comprising, for example, a blend of: (a) at least one first post-consumer recycled resin; (b) at least one second post-consumer recycled resin; and (c) at least one virgin low density polyethylene; and, if desired, (d) any optional additives other than components (a), (b) and (c).

[0039] In a preferred embodiment, the formulated resin comprises:

[0040] (a) at least one first post-consumer recycled (PCR1) resin derived from a recycled high density polyethylene (r-HDPE) resin; wherein the at least one PCR1 resin has a density of 0.940 g / cc to 0.970 g / cc and a melt index I2 of 0.01 g / 10 min to 1.0 g / 10 min;

[0041] (b) at least one second post-consumer recycled (PCR2) resin derived from a recycled low density polyethylene (r-LDPE) resin; wherein the at least one PCR2 resin has a density of 0.915 g / cc to 0.935 g / cc and a melt index I2 of 0.1 g / 10 min to 2.0 g / 10 min;

[0042] (c) at least one virgin low density polyethylene (v-LDPE) resin; wherein the at least one v-

[0043] The LDPE resin has a density of 0.915 g / cc to 0.925 g / cc and a melt index I2 of 0.1 g / 10 min to 1 g / 10 min; and

[0044] If desired, (d) is different from any optional additives of components (a), (b) and (c).

[0045] In some embodiments, the polymer resin blend composition (ie, r-HDPE + r-LDPE + v-LDPE resins) is advantageously used to make CSF products. In one embodiment, the resulting CSF is a fully recyclable polyethylene structure.

[0046] Before manufacturing CSF products from the polymer blend formulation, the blend formulation is first processed into pellets. For example, the materials forming the blend formulation are melt blended (by melt mixing, such as via an extruder) to produce a melt blend formulation. The melt blend formulation is then fed from an extruder (e.g., a twin-screw extruder) through a strand die into a pelletizer to form pellets of the blend formulation. Once made, the pellets are then processed to manufacture a CSF product having desired shrinkage characteristics.

[0047] The at least one first post-consumer recycled (PCR1) resin, component (a), useful in the formulated blend formulation of the present invention includes, for example, one or more recycled polymer resins, wherein the recycled polymer resin is selected from the group consisting of LLDPE, LDPE, HDPE, polypropylene (PP), polyamide (PA), ethylene vinyl alcohol (EVOH), polyethylene terephthalate (PET), and mixtures thereof. In a preferred embodiment, the PCR1 resin includes, for example, recycled HDPE, recycled LDPE, recycled LLDPE, and mixtures thereof. In another embodiment, the at least one PCR1 resin is a recycled HDPE resin, wherein the recycled HDPE resin has a density of 0.940 g / cc to 0.970 g / cc and a melt index I2 of 0.01 g / 10 min to 1.0 g / 10 min.

[0048] Typically, the PCR1 resin is derived from recycled high-density polyethylene resin (r-HDPE). For example, r-HDPE is derived from packaging waste, such as material generated by households or by commercial, industrial and institutional facilities as end users of the product. In a preferred embodiment, the PCR1 resin is derived from plastic containers, such as plastic bottles made from HDPE.

[0049] In some embodiments, the density of the PCR1 resin is generally from 0.94 g / cc to 0.97 g / cc in one general embodiment; from 0.945 g / cc to 0.965 g / cc in another embodiment; and from 0.95 g / cc to 0.96 g / cc in yet another embodiment.

[0050] In some embodiments, the melt index of the PCR1 resin is in the range of 0.01 g / 10 min to 1 g / 10 min in one general embodiment; in the range of 0.05 g / 10 min to 1 g / 10 min in another embodiment; and in the range of 0.01 g / 10 min to 0.5 g / 10 min in yet another embodiment.

[0051] The PCR1 resin used in the blend formulation or formulated resin, i.e., component (a), may be present in the formulated resin typically in an amount of 20 wt % to 50 wt % in one embodiment; 20 wt % to 40 wt % in another embodiment; and 25 wt % to 35 wt % in yet another embodiment, based on the total amount of components in the blend formulation.

[0052] The at least one second post-consumer recycled (PCR2) resin, component (b), useful in the formulated blend formulations of the present invention includes, for example, one or more recycled polymer resins, wherein the recycled polymer resin is selected from the group consisting of LLDPE, LDPE, HDPE, PP, PA, EVOH, PET, and mixtures thereof. In a preferred embodiment, the PCR2 resin includes, for example, recycled HDPE, recycled LDPE, recycled LLDPE, and mixtures thereof.

[0053] In another embodiment, at least one PCR2 resin is a recycled LDPE; wherein the recycled LDPE resin has a density of 0.915 g / cc to 0.935 g / cc and a melt index I2 of 0.1 g / 10 min to 2.0 g / 10 min.

[0054] Typically, the PCR2 resin is derived from recycled low-density polyethylene (r-LDPE) resin. For example, the r-LDPE resin is derived from packaging waste, such as material generated by households or by commercial, industrial and institutional facilities as end users of the product. In a preferred embodiment, the PCR2 resin is derived from flexible packaging films (e.g., shrink films, logistics films, stretch films, etc.) made from LDPE.

[0055] In some embodiments, the density of the PCR2 resin is generally from 0.915 g / cc to 0.935 g / cc in one general embodiment; from 0.916 g / cc to 0.935 g / cc in another embodiment; and from 0.918 g / cc to 0.933 g / cc in yet another embodiment.

[0056] In some embodiments, the melt index of the PCR2 resin is in the range of 0.1 g / 10 min to 2.0 g / 10 min in one general embodiment; in the range of 0.2 g / 10 min to 1 g / 10 min in another embodiment; and in the range of 0.5 g / 10 min to 2.0 g / 10 min in yet another embodiment.

[0057] Based on the total amount of components in the blend formulation, the PCR2 resin used in the blend formulation or formulated resin, i.e., component (b), may be present in the formulated resin in an amount typically from 20 wt % to 70 wt % in one embodiment; from 25 wt % to 65 wt % in another embodiment; and from 30 wt % to 60 wt % in yet another embodiment.

[0058] Component (c) of the formulated resin comprises at least one virgin low density polyethylene (v-LDPE) resin; wherein the at least one v-LDPE resin has a density of 0.915 g / cc to 0.925 g / cc and a melt index I2 of 0.1 g / 10 min to 1 g / 10 min.

[0059] The original LDPE resins used in combination with the PCR1 resin and the PCR2 resin to form the blend formulations of the present invention include, for example, LDPE 150E, LDPE 310E, LDPE 132I, LDPE 611A, AGILITY TM 1500、AGILITY TM 2000、AGILITY TM 2001 (both available from The Dow Chemical Company), and mixtures thereof. In a preferred embodiment, the v-LDPE resin may include, for example, LDPE 150E.

[0060] In other embodiments, the v-LDPE resin may also include commercially available compounds such as LDPE 2420D (available from Sinopec Maoming), LUPOLEN LDPE 2420D (available from Lyondellbasell), LDPE LD163 (available from Sinopec Yanshan), and LDPE 1810D (available from CNPC Daqing); and mixtures thereof.

[0061] When used in a blend formulation, the LDPE resin may be present in an amount of typically 10 wt % to 40 wt % in one embodiment; 20 wt % to 40 wt % in another embodiment, and 25 wt % to 35 wt % in yet another embodiment, based on the total amount of components in the blend formulation.

[0062] In another embodiment, the blend formulation or formulated resin of the present invention may include a variety of other optional additives. The additives combined with the composition of the present invention can be formulated to achieve the performance of specific functions while maintaining the excellent benefits / characteristics of the blend formulation. For example, the following additives can be blended into the formulated resin to form the CSF formulation of the present invention, including: antioxidants, pigments, colorants, UV stabilizers, UV absorbers, processing aids, fillers, slip agents, anti-caking agents, etc.; and mixtures thereof.

[0063] When used in a blend formulation, the optional additives may be present in an amount generally ranging from 0% to 10% by weight in one embodiment, in an amount ranging from about 0.1% to 5% by weight in another embodiment, and in an amount ranging from 1% to 3% by weight in yet another embodiment, based on the total amount of components in the blend formulation. In other embodiments, the optional additives may be added to the blend formulation in an amount less than 5% by weight in one general embodiment, less than 3% by weight in another embodiment, and less than 1% by weight in yet another embodiment.

[0064] In a broad embodiment of the present invention, a process for making a blend formulation or formulated resin includes, for example, mixing or blending the above components (a), (b) and (c); and any desired optional component (d) other than the above components (a), (b) and (c). Both dry blending and compounding processes known to those skilled in the art of mixed polymer resins can be used. In a preferred embodiment, a compounding process is used.

[0065] Typically, the dry mixing process includes the following steps:

[0066] Step (1): weighing each of the above-mentioned polymer resin components (a), (b), (c) and optional component (d) provided in the form of pellets in the correct proportion; and

[0067] Step (2): Mix all the polymer pellets together using a tumble blender or a ribbon blender or any equivalent dry blender.

[0068] Typically, the compounding (or melt blending) process includes the following steps:

[0069] Step (1): feeding polymer pellets of all components (a), (b), (c) and optionally component (d) at feed rates proportional to the corresponding ratios;

[0070] Step (2): melt mixing the polymer pellets in a twin-screw extruder or a single-screw extruder or a continuous mixer or a batch mixer to form a homogeneous melt;

[0071] Step (3): filtering the polymer melt using a polymer melt screen changer; and

[0072] Step (4): pelletizing the filtered polymer melt into final blended pellets using, for example, an underwater pelletizer, a strand pelletizer or a hot melt pelletizer.

[0073] In a preferred embodiment of the present invention, a process for making a blend formulation comprises, for example, the following steps:

[0074] (I) providing the above-mentioned components (a), (b), (c) and optionally component (d); and

[0075] (II) mixing or blending or compounding the components (a), (b) and (c) of step (I) at a temperature of 160° C. to 275° C. and a pressure of 5,515 kPa (800 psi) to 22,063 kPa (3,200 psi) in a mixing apparatus known in the art such as an extruder, a batch mixer or a continuous mixer.

[0076] (b), (c) and optionally component (d).

[0077] Some advantageous / beneficial properties exhibited by the blend formulations made according to the process of the present invention may include, for example: the blend formulations can be easily produced, i.e., the different components (a), (b), (c) and optional component (d) of the blend can be easily and more evenly (consistently or homogeneously) dispersed; and the processability of the blend formulations is improved, i.e., CSF films can be easily manufactured by easily processing the blend formulations. The blends also exhibit exceptionally improved aesthetics (e.g., reduced gel / defect counts) when made into films, while maintaining other mechanical and thermal properties of the films to meet the requirements of the target application.

[0078] After preparing the blend formulation by compounding components (a), (b), (c) and optional component (d) as described above, the blend formulation is processed to form a pellet or granule, also referred to as a pre-made pellet or a nutrient granule (nurdle). For example, the material forming the blend formulation is melt blended (by melt mixing, for example, via an extruder) to manufacture the formulation. Then, the melt blend formulation is sent from an extruder (for example, a twin screw extruder) through a strand die into a granulator to form a pellet of the blend formulation. Once made, pellets are used to manufacture a shrink film with desired shrinkage characteristics. By granulating the blend formulation, the complexity of the process of converting pellets into a film becomes lower and easier to carry out.

[0079] In a preferred embodiment, a process for making pellets comprises, for example, the following steps:

[0080] (I) providing the above-mentioned components (a), (b), (c) and optionally component (d);

[0081] (II) in a mixing device (e.g., a twin-screw extruder) at a melt temperature (e.g.,

[0082] 160° C. to 275° C.) at a temperature of 160° C. to 275° C.; and

[0083] (III) forming blended formulation pellets from the mixture of step (II).

[0084] Step (III) of the above process, i.e., forming pellets of the blended formulation, comprises pelletizing the mixture or compounded blended formulation from step (II) using a pelletizer, which is a device known in the art of making pellets. For example, pellets for making the shrink film of the present invention are obtained by heating and melting the polymer blend formulation and extruding the molten material into a strand form, and then cutting the resulting strand into small pieces, i.e., so-called pellets.

[0085] The size of pellets made from the pelletized compounded blend formulation is generally from 1.0 mm to 4.0 mm in one embodiment, from 2.0 mm to 3.5 mm in another embodiment, and from 2.5 mm to 3.5 mm in yet another embodiment.

[0086] When using the pellets as described above to make shrink films, these pellets have many advantages. For example, the pellets show improved melt strength and reduced defect counts.

[0087] Generally, the melt strength of the pellets is greater than or equal to 15 cN in one embodiment, from 15 cN to 30 cN in another embodiment, and from 15 cN to 25 cN in yet another embodiment.

[0088] Various known methods and apparatus known in the art for measuring the melt strength of pellets can be used. In one embodiment, for example, melt strength (MS) measurements of pellets are performed on a Gottfert Rheotens 71.97 (available from Gottfert Inc.; Rock Hill, SC) attached to a Gottfert Rheotester 2000 or Rheograph 25 capillary rheometer. The MS test method is described in detail in the Examples.

[0089] Defect Count (DC) number is a measure of the number of defects detected in extruded film using optical imaging technology in accordance with the procedures and guidelines in ASTM D7310-20 "Standard Practice for Defect Detection and Rating of Plastic Film Using Optical Sensors". The DC number is reported as the number of defects detected in extruded film in the case of an effective circle diameter within a series of user-defined ranges as follows: 3 The number of optical defects: for example, 200 μm to 400 μm, 400 μm to 800 μm, 800 μm to 1600 μm, and 1600 μm and above. The method of measuring the DC number is described in detail in the Examples.

[0090] The present invention also includes producing collation shrink films made from the above blend formulations and blend formulation pellets. The collation shrink films of the present invention have a combination of good aesthetics (reduced defect counts), toughness (puncture resistance, dart impact and tear strength), stiffness (secant modulus), shrinkage force, compaction force, shrinkage and processability. The characteristic of the shrink film is that the film shrinks anisotropically, for example, the shrink film can shrink 65% to 85% in the machine direction (MD). By wrapping the article circumferentially so that the MD direction of the shrink film is oriented in the circumferential wrapping direction, the higher shrinkage, shrinkage and compaction forces in the MD are advantageously utilized.

[0091] In one broad embodiment, the method of making the shrink film of the present invention comprises the following steps:

[0092] (I) melt blending at least one post-consumer recycled resin component (a), at least one post-consumer recycled resin component (b), at least one virgin low density polyethylene resin component (c), and any optional additives to produce a formulated resin; and

[0093] (II) forming at least one monolayer or multilayer film using blown film extrusion, wherein at least one layer of the extruded film comprises a formulated resin.

[0094] In a preferred embodiment, the CSF of the present invention is manufactured using a blown film process known to those skilled in the art of film manufacturing. The blown film process for manufacturing a blown shrink film generally includes one or more of the following steps: step (1) providing dry pellets of the blend formulation, step (2) melting the pellets to form a melt, step (3) forming heated bubbles from the resulting melt, step (4) collapsing the bubbles to form a blown film, and step (5) cutting the collapsed bubbles to form a film member or a sheet member. In addition, the step of forming the heated bubbles may include a stretching step to orient the film.

[0095] In another preferred embodiment, CSF is produced using a blown film process, including, for example: (I) providing dry pellets of a blend formulation, (II) melting the pellets to form a melt, (III) extruding the resulting melt using an extrusion process, and (IV) processing the extruded material by a blown film process to form a shrink film. Optionally and preferably, the blended formulation pellets are first dried by heating in a dryer to remove surface moisture. The melting step may be performed at a temperature of 165° C. to 230° C. in one embodiment; at a temperature of 170° C. to 200° C. in another embodiment; and at a temperature of 175° C. to 200° C. in yet another embodiment. Extrusion of the blend formulation may be performed through a T-die.

[0096] In a broad embodiment of the invention, the above blend formulation is used to make a film. The film composition is described above. The film monolayer structure includes, for example, a film sheet of any desired length and width; and has, for example, a thickness of 20 μm to 100 μm in one embodiment; a thickness of 25 μm to 90 μm in another embodiment; and a thickness of 30 μm to 80 μm in yet another embodiment.

[0097] In one broad embodiment of the present invention, a method of making a monolayer film comprises, for example, using any conventional film forming method, such as a blown film method and equipment well known to those skilled in the art of film forming.

[0098] In some embodiments, the collation shrink film may include two or more film substrates combined together to form a CSF for shrink-wrapping an article. For example, the shrink film may be made of three, five, seven, nine or more layers. In one embodiment, the CSF includes a three-layer film structure including two skin layers and a core layer disposed between the two skin layers. In another embodiment, the CSF may be a five-layer film structure including a core layer disposed between two sub-skin layers; and each of the sub-skin layers may be disposed between the core layer and the outer skin layer.

[0099] As described above, the polymer blend formulation or composition for making a shrink film product comprises: (a) at least one first post-consumer recycled (PCR1) resin, (b) at least one second post-consumer recycled (PCR2) resin, and (c) at least one virgin low-density polyethylene (v-LDPE) resin; and at least one of the layers of the film structure is at least one layer comprising the blend formulation or formulated resin.

[0100] For example, a 3-layer finishing shrink film having an A / B / A film structure can be prepared; and the 3-layer finishing shrink film can have a first skin layer A, a core layer, and a second skin layer A in a ratio of 1:2:1, respectively. Although a 3-layer finishing shrink film is a preferred embodiment, the present invention includes a multilayer film member having any number of film layers, as long as at least one layer of the multilayer film member includes a film layer containing a PCR resin of the present invention, such as a core layer; and wherein the film layer containing a PCR resin has an appropriate balance of properties such as stiffness, toughness, and shrinkage. In one embodiment, the film structure of the multilayer film member can be an A / B / A film, wherein each A is a skin layer of the same material; and B is a core layer disposed between two skin layers A. In another embodiment, the structure of the multilayer film member can be an A / B / A' film, wherein A is a first skin layer and A' is a second skin layer of a different material from the first skin layer A; and B is a core layer located between skin layer A and skin layer A'. In another embodiment, the structure of the multilayer film member can be any combination of A, B, and A' layers, which will be apparent to those skilled in the art of film manufacturing.

[0101] Similarly, a five-layer collation shrink film having a film structure of A / B / C / B' / A' can be prepared, wherein A is the skin or outermost layer of the film; B is a sub-skin layer that promotes toughness; C is the core layer; B' is another sub-skin layer that promotes toughness; and A is the innermost layer of the film. Sub-skin layer B is disposed between outer layer A and core layer C; and another sub-skin layer B' is disposed between inner layer A' and core layer C. Outer layer A and inner layer A' can be made of the same material or different materials. Sub-skin layer B and sub-skin layer B' can be made of the same material or different materials.

[0102] For the various films described herein, the A and A' layers may be formed of any material known in the art for multilayer films. Thus, for example, the A layer and / or the A' layer may be formed of polyethylene (homopolymer or copolymer) or a blend of two or more polyethylene polymers; and the polyethylene may be selected from the group consisting of, for example, VLDPE, LDPE, LLDPE, MDPE, HDPE, and mixtures thereof, and other polyethylenes known in the art. For another example, the A and / or A' layers may be formed of polyethylene (homopolymer or copolymer), a non-polyethylene polymer (e.g., polypropylene), or a blend of polyethylene, a non-polyethylene polymer, and a mixture thereof.

[0103] In a multilayer film structure, one or more of the B layer and / or the B' layer as a sub-skin layer promoting toughness may include, for example, INNATE TM ST50 Precision Packaging Resin (available from The Dow Chemical Company); ethylene vinyl acetate copolymer; and mixtures thereof.

[0104] In some preferred embodiments, the core layer of the three-layer CSF structure and the five-layer CSF structure includes a layer made from a polymer blend formulation as described above, that is, wherein the formulated resin includes (a) at least one PCR1 resin, (b) at least one PCR2 resin and (c) at least one v-LDPE resin; and if desired, any optional additives.

[0105] As an illustration of the film structure, but not limited thereto, a three-layer film structure of A / B / A' configuration is described below, where A is the first surface layer, B is the core layer, and A' is the second surface layer. For example, the surface layer A of the CSF product can be made of one or more materials, including, for example, HDPE, LDPE, MDPE, LLDPE, and mixtures thereof. In a preferred embodiment, the material of at least one first surface layer that can be used in the present invention can be HDPE, LDPE, LLDPE, and mixtures thereof.

[0106] Some exemplary commercially available materials that can be used in the first skin layer of the present invention can include, for example, DOWLEX TM 2045G、DOWLEX TM NG 5045P、DOWLEX TM 2645G, DOWEX TM 2049G、DOWLEX TM 2038.68G, DMDA-6200NT 7, DMDA-6400NT 7, DOWLEX GM 8070G, LDPE 611A, AGILITY TM 2000、AGILITY TM 1023、DOW TM LDPE 150E and DOW TM LDPE 310E (both available from The Dow Chemical Company); ENABLE TM 2703 and ENABLE TM 3505 (both available from ExxonMobil); LUTENE TM BE0400 (available from LG Chem); and mixtures thereof.

[0107] The thickness of the first skin layer used in the film of the present invention is, for example, 8 to 30 μm in one embodiment, 10 to 25 μm in another embodiment, and 12 to 20 μm in yet another embodiment.

[0108] In a preferred embodiment, the first skin layer is a combination of LDPE, LLDPE and HDPE. LDPE has a density of 0.915 g / cc to 0.925 g / cc and a melt index I2 of 0.1 g / 10 min to 2 g / 10 min; LLDPE has a density of 0.915 g / cc to 0.94 g / cc and a melt index I2 of 0.2 g / 10 min to 2 g / 10 min; and HDPE has a density of 0.945 g / cc to 0.965 g / cc and a melt index I2 of 0.04 g / 1 min to 1 g / 10 min.

[0109] The second surface layer A' of the film of the present invention can be made of the same material as the first surface layer A described above; or in an alternative embodiment, the second surface layer A' can be made of one or more materials different from the first surface layer A, including, for example, HDPE, LDPE, LLDPE, MDPE, and mixtures thereof. In a preferred embodiment, the material of the second surface layer that can be used in the present invention can be a material selected from the group consisting of HDPE, LDPE, LLDPE, and mixtures thereof. In another preferred embodiment, the material of the second surface layer A' is the same as the material of the first surface layer A.

[0110] Some exemplary commercially available materials that can be used in the second skin layer of the present invention can include, for example, DOWLEX TM 2045G、DOWLEX TM NG 5045P、DOWLEX TM 2645G, DOWEX TM 2049G、DOWLEX TM 2038.68G, DMDA-6200NT 7, DMDA-6400NT 7, DOWLEX GM 8070G, LDPE 611A, AGILITY TM 2000、AGILITY TM 1023、DOW TM LDPE 150E and DOW TM LDPE 310E (both available from The Dow Chemical Company); ENABLE TM 2703 and ENABLE TM 3505 (both available from ExxonMobil); LUTENE TM BE0400 (available from LG Chem); and mixtures thereof.

[0111] The thickness of the second skin layer used in the film of the present invention is, for example, 8 to 30 μm in one embodiment, 10 to 25 μm in another embodiment, and 12 to 20 μm in yet another embodiment.

[0112] In a preferred embodiment, the second skin layer can be made of a combination of LDPE and LLDPE. The LDPE can have a density of 0.915 g / cc to 0.925 g / cc and a melt index I2 of 0.1 g / 10 min to 2 g / 10 min; and the LLDPE can have a density of 0.915 g / cc to 0.94 g / cc and a melt index I2 of 0.2 g / 10 min to 2 g / 10 min.

[0113] The core layer B containing PCR resin of the film of the present invention (i.e., the middle layer containing PCR resin disposed between the first skin layer and the second skin layer) is made of one or more materials, including, for example, HDPE, MDPE, LDPE, LLDPE and mixtures thereof, as long as at least two polymers are derived from recycled polymers or materials. In a preferred embodiment, the recycled polymer material of the core layer B that can be used in the present invention may include r-HDPE, r-LDPE and mixtures thereof.

[0114] Some exemplary commercially available materials that can be used in the core layer containing PCR resin of the present invention can include, for example, DOWLEX TM 2045G、DOWLEX TM NG 5045P、DOWLEX TM 2645G, DOWEX TM 2049G、DOWLEX TM 2038.68G, DMDA-6200NT 7, DMDA-6400NT 7, TUFLIN TM HS-7072、DOW TM LDPE 150E, DOW TM LDPE 310E, DOW TM LDPE132I、AGILITY TM 2000 and AGILITY TM 1500 (both available from The Dow Chemical Company); ENABLE TM 2703 and ENABLE TM 3505 (both available from ExxonMobil); LUTENE TM BE0400 (available from LG Chem); and mixtures thereof.

[0115] The thickness of the core layer containing PCR resin used in the film of the present invention is, for example, 20 to 60 μm in one embodiment, 25 to 55 μm in another embodiment, and 30 to 50 μm in yet another embodiment.

[0116] The PCR resin loading level of the PCR resin-containing core layer is typically from 10 wt% to 80 wt% in one embodiment, and from 10 wt% to 70 wt% in another embodiment.

[0117] The density of the core layer comprising PCR resin is generally from 0.925 g / cc to 0.940 g / cc in one embodiment, from 0.930 g / cc to 0.940 g / cc in another embodiment, and from 0.930 g / cc to 0.935 g / cc in yet another embodiment.

[0118] The melt index of the core layer containing PCR resin is generally from 0.1 g / 10 min to 1.0 g / 10 min in one embodiment, from 0.15 g / 10 min to 0.8 g / 10 min in another embodiment, and from 0.15 g / 10 min to 0.5 g / 10 min in yet another embodiment.

[0119] In a broad embodiment of the invention, a method of making the film of the invention comprises, for example, using any conventional film forming method, such as a blown film method and equipment well known to those skilled in the art of film forming. Typically, for example, a blown film process is used to make CSF. As an illustration of a blown film process but not limited thereto, a blown film having a layer ratio of 1 / 2 / 1, such as the three-layer film described herein and prepared in the examples herein below, can be produced on a conventional blow molding line (e.g., a blow molding line manufactured by Battenfeld Gloucester) using typical manufacturing parameters readily determined by those skilled in the art of producing blown films.

[0120] Some of the advantageous properties exhibited by the CSF product prepared by the above method of the present invention may include, for example, good shrinkage performance as measured by shrinkage force and compaction force, wherein the shrinkage force in the machine direction is greater than 100 mN and wherein the compaction force is greater than 2,500 mN (ISO 14616). The CSF product also exhibits good toughness as measured by puncture resistance, dart impact resistance, and Elmendorf tear strength, wherein the puncture resistance is greater than 3.3 MPa (40 ft*lbf / in 2) as measured by the procedure described in ASTM D5748. 3), wherein the dart impact resistance is greater than 70 g as measured by the procedure described in ASTM D1709 Type A, and wherein the Elmendorf tear strength in the machine direction is greater than 100 gf as measured by the procedure described in ASTM D1922 Type B (constant radius). The CSF product also exhibits good processability, as measured by melt strength, wherein the melt strength is greater than 15 cN. The CSF product prepared as described above can be used, for example, in packaging applications.

[0121] In a preferred embodiment, a CSF structure incorporating a certain amount of PCR resin (eg, 70% PCR resin) can have similar properties compared to films made from polyethylene virgin resin (eg, virgin LDPE resin).

[0122] The collation shrink film of the present invention is a packaging film used to collate multiple groups of articles into an integrated package for handling, shipping, distribution and final sale. Non-limiting examples of articles that can be wrapped with the collation shrink film include: food cans; bottles or cans of beverages such as water, soft drinks, beer, energy drinks and liquid protein drinks; and bottles or cans of multipacks.

[0123] Typically, a collation shrink film is applied to (e.g., wrapped around) one or more articles or items, and the shrink film with the wrapped articles or items is then placed under a heat source to shrink the film, resulting in an integrated package of the wrapped articles / items ready for handling, shipping, distribution, and ultimate sale. Suitable performance characteristics on a shrink packaging line include sufficient stiffness to allow the film to wrap properly around the packaged article, sufficient dimensional shrinkage to ensure a tight fit, and a sufficiently low coefficient of friction (COF) for machinability and packaging handling.

[0124] As shown in the following examples, the collation shrink film of the present invention has high heat shrinkage to ensure a tight fit and high tensile strength to withstand handling and excessive use during transportation. In addition, the packaging has excellent display properties, including haze (or "contact clarity") and clarity ("see-through clarity"). In addition, other characteristics such as low melt pressure and the ability to use low motor power are characteristics that advantageously allow film manufacturers to provide higher productivity.

[0125] Example

[0126] The following Inv.Ex. and Comp.Ex. (collectively referred to as "Examples") are given herein to further illustrate the features of the present invention, but are not intended to be construed as limiting the scope of the claims, either explicitly or by implication. The Inv.Ex. of the present invention are represented by Arabic numerals, and the Comp.Ex. are represented by letters of the alphabet. The following experiments analyze the performance of the embodiments of the compositions described herein. Unless otherwise indicated, all parts and percentages stated are by weight based on total weight.

[0127] The various terms, names and raw materials used in the examples of the present invention (Inv.Ex.) and comparative examples (Comp.Ex.) are explained as follows:

[0128] “PCR” stands for post-consumer recycled.

[0129] "LDPE" stands for low-density polyethylene.

[0130] "HDPE" stands for high-density polyethylene.

[0131] "r-LDPE natural" stands for recycled low-density polyethylene.

[0132] "r-HDPE natural" stands for recycled high-density polyethylene.

[0133] With respect to resins, "natural" means that no pigments are present in the resin.

[0134] raw materials

[0135] The ingredients / raw materials used in the examples are explained as follows:

[0136] "PCR1" is a post-consumer recycled resin material having a formulation of r-LDPE Natural 510A / r-HDPE Natural 921D / LDPE 150E (50 / 30 / 20 respectively) and having a PCR resin loading of 80 wt%.

[0137] "PCR2" is a post-consumer recycled resin material having a formulation of r-LDPE Natural 510A / r-HDPE Natural 921D / LDPE 150E (40 / 30 / 30 respectively) and having a PCR resin loading of 70 wt%.

[0138] "Resin A" is a control resin having a single source PCR resin with a loading of up to 40 wt%; Resin A is available from The Dow Chemical Company under the trade name XUS 60921.01.

[0139] LDPE 150E (resin B) is a low density polyethylene resin available from The Dow Chemical Company.

[0140] r-LDPE Natural 510A (resin C) is a recycled low density polyethylene resin material available from PT Elite. The term "natural" specified in the above polymer means that the color of the resin is natural color.

[0141] r-HDPE Natural 921D (resin D) is a recycled high density polyethylene resin material available from PT Elite. The term "natural" specified in the above polymer means that the color of the resin is natural color.

[0142] Some characteristics of the ingredients / raw materials used in the examples are described in Table I.

[0143] Table I - Characteristics of raw materials

[0144]

[0145]

[0146] Resin preparation

[0147] General procedure for preparing resin formulations

[0148] The polymer resin formulation samples described in Table II were compounded according to the following general procedure:

[0149] To prepare the polymer resin formulation, various polymer pellets (PCR resin pellets and virgin polymer pellets) were melt blended in a co-rotating twin screw extruder (TSE), a single screw extruder (SSE), a continuous mixer or a Banbury batch mixer. A 40mm Coperion co-rotating twin screw extruder with an L / D of 44 was used to melt mix and homogenize the polymer resin formulation. Various polyethylene (PCR resin and virgin resin) pellets were fed into the feed hopper of the TSE funnel using a separate K-Tron gravimetric feeder. The TSE barrel was set to a temperature between ambient temperature and 240°C, and the screw speed of the extruder was set at 300rpm. The polymer pellets were fed at a rate proportional to the formulation, with a total material throughput rate of 200lb / hr (0.0252Kg / s). The final polymer pellets were melt mixed in the TSE and subsequently melt filtered using a polymer melt screen changer with a 20 / 40 / 100 / 40 / 20 mesh screen configuration. The filtered polymer melt was then pelletized using a Gala underwater pelletizer to provide pellets having a particle size corresponding to 32 particles / g.

[0150] In one embodiment, the PCR1 resin blend formulation prepared according to the general procedure above has the following composition: PCR1 resin is an 80% PCR resin formulation having a 50 / 30 / 20 blend corresponding to r-LDPE Natural 510A / r-HDPE Natural 921D / LDPE 150E.

[0151] In another embodiment, a PCR2 resin blend formulation prepared according to the general procedure above has the following composition: PCR2 resin is a 70% PCR resin formulation having a 40 / 30 / 30 blend corresponding to r-LDPE Natural 510A / r-HDPE Natural 921D / LDPE 150E.

[0152] Resin A is a PCR resin containing 40% HDPE PCR resin; and Resin A (XUS 60921.01) is commercially available from The Dow Chemical Company.

[0153] Resin B, Resin C and Resin D are DOW TM LDPE 150E resin, r-LDPE natural 510A resin, and r-HDPE natural 921D resin were used “as is” as received from the suppliers.

[0154] The resin formulations used to make the various CSF samples tested are described in Table II.

[0155] Table II - Resin Formulations

[0156]

[0157] Membrane samples

[0158] General procedure for preparing CSF

[0159] The CSF sample used in the embodiment is a blown film, and the CSF is manufactured using a blown film process. Each CSF sample film has a three-layer film structure of A / B / A (surface layer / core layer / surface layer) structure with a layer ratio of 1 / 2 / 1 or 25 / 50 / 25. Each CSF sample film has a total thickness of 60 μm. Each surface layer A has a film structure of 40 / 40 / 20DOWLEX 2045G / LDPE 150E / DMDA 6400. The core layer B of each CSF sample is used to distinguish between the comparative example and the embodiment of the present invention. The following four films with an A / B / C film structure are used as core layer B:

[0160] Film #1 - Reference: 44 / 40 / 20 DOWLEX 2038.68G / LDPE 150E / DMDA 6400.

[0161] Membrane #2 - Control: XUS 60921.01.

[0162] Film #3 - 80% PCR: compounded 50 / 30 / 20 corresponding to r-LDPE Natural 510A / r-HDPE Natural 921D / LDPE 150E.

[0163] Film #4 - 70% PCR: compounded 40 / 30 / 30 corresponding to r-LDPE Natural 510A / r-HDPE Natural 921D / LDPE 150E.

[0164] The 3-layer (A / B / C structure) CSF film samples were blown using the Alpine production line manufactured by Hosokawa Alpine. The film manufacturing parameters / conditions were as follows:

[0165] (1) Blowing ratio (BUR): 3.0

[0166] (2) Specification: 2.36 mil (60 μm)

[0167] (3) Die gap: 78.7 mils (2.0 mm)

[0168] (4) Die size: 9.84 inches (250 mm)

[0169] (5) Output: 140.6 kg / hr (310 lbs / hr)

[0170] (6) Line speed: 60ft / min (0.3048m / s)

[0171] (7) Stretch ratio: 11.1

[0172] The formulations described in Table II were used to make the various CSF samples described in Table III.

[0173] Table III - Collation Shrink Film

[0174]

[0175] Test Method

[0176] density

[0177] Unless otherwise stated, all densities disclosed herein are measured according to ASTM D792-08 Method B and are expressed in grams per cubic centimeter (g / cm 3 or g / cc).

[0178] Melt index (I2)

[0179] Unless otherwise stated, all melt indices (I2) disclosed herein are measured according to ASTM D1238-10 Method B at 190°C and 2.16 kg load and are reported in grams eluted per 10 minutes (g / 10 min).

[0180] Melt flow rate (I 10 )

[0181] Unless otherwise stated, all melt flow rates (MFRs) disclosed herein are 10 ) are measured according to ASTM D1238-10 Method B at 190°C and 10 kg load and are reported in grams eluted per 10 minutes (g / 10 min).

[0182] Melt Strength

[0183] Melt strength (MS) measurements were performed on a Gottfert Rheotens 71.97 (available from Gottfert Inc.; Rock Hill, SC) attached to a Gottfert Rheotester 2000 or Rheograph 25 capillary rheometer. Rheotester 2000 capillary rheometer, by feeding the polymer melt of the pellets into The MS of the pellets was measured at 190°C in a Rheotens 71.97, which was equipped with a flat inlet angle (180 degrees) with a length of 30 mm, a diameter of 2 mm and an aspect ratio (capillary length / capillary diameter) of 15. The blended formulation melt (e.g., about 20 g to 30 g, pellets) was extruded through a capillary die. The pellets were fed into a barrel (L = 300 mm, diameter = 12 mm), compressed and allowed to melt at 190°C for 10 minutes, and then extruded at a constant piston speed of 0.265 mm / s, which corresponds to 38.2 s at a given die diameter. -1 The extrudate passes through a Rheotens wheel located 100 mm below the die exit and the extrudate passes through the wheel at a shear rate of 2.4 mm / s. 2 The force applied to the wheel (in cN) is recorded as a function of wheel speed (in mm / s). Melt strength is reported as the plateau force (cN) before the strand breaks. Drawability is the maximum speed at which the polymer chain breaks.

[0184] Defect count number

[0185] The Defect Count (DC) number is a measure of the number of defects detected in extruded film using optical imaging technology in accordance with the procedures and guidelines in ASTM D7310-20 "Standard Practice for Defect Detection and Rating of Plastic Film Using Optical Sensors". The DC number is reported as the number of defects detected in extruded film in the case of effective circle diameter within a range of user-defined ranges per 24.6 cm 3 The number of optical defects is measured by an optical control system (OCS) film surface analyzer FSA100 (OCSFSA100) optical imaging system. The OCS FSA100 optical imaging system consists of an illumination unit (e.g., a halogen-based source light), a charge coupled device (CCD) line scan camera, and a computer with image / data analysis software version 5.0.4.6.

[0186] The OCS FSA100 optical imaging system detects defects because they obscure the transmission of the halogen-based source light. The average grayscale is set to 170 and the threshold sensitivity is set to 35%. In addition, the gain of the CCD system is adjusted to compensate for film haze. The imaging system creates a composite area for each defect by adding the defect pixels from each subsequent line scan. The system then reports the number of defects within the above user-defined size range based on the diameter of a circle with equivalent area.

[0187] In one embodiment, the defect has an equivalent circular diameter (per 24.6 cm) in the range of 200 μm to 400 μm when measured according to the methods described herein. 3 The DC number of the defect measured in the film is less than or equal to 20,000; and in another embodiment, when measured according to the method described herein, the defect has an equivalent circular diameter (per 24.6 cm) in the range of 400 μm to 800 μm. 3 The DC number of the membrane) is less than or equal to 1,000.

[0188] Film manufacturing is completed by an OCS ME19 cast film extrusion system equipped with a fixed lip coat hanger die. The die gap is 500μm×15cm. The extruder is used as a single screw extruder equipped with a 19mm screw provided by OCS. The screw design is a 3:1L / D compression ratio with a pineapple mixing tip. The total extrusion system mass output is 10kg / hr±5kg / hr. The film thickness is prepared to be 38μm, which is achieved by adjusting the cooling roller. Nitrogen purging is used at the feed throat of the extruder. The temperature distribution of extrusion is in the range of 135°C to 190°C to achieve a target extrusion pressure of 220 bar to 240 bar.

[0189] Machinability

[0190] When making films on the Alpine line, the processability of the CSF made as described above was measured by the average head pressure before the screen pack. The average head pressure before the screen pack and the average pressure after the screen are two melt pressures read from two different locations on each extruder. The first reading is measured after the extruder and just before the screen changer. The second reading is taken after the screen changer.

[0191] Haze

[0192] Film haze was measured using BYK Haze-Gard plus according to ASTM D1003. After film preparation, the film was conditioned at 23°C (+ / -2°C) and 50% relative humidity (RH) (+ / -10%) for at least 40 hours according to ASTM standards. According to ASTM standards, standard test conditions are 23°C (+ / -2°C) and 50% RH (+ / -10%).

[0193] For each sample to be tested, five separate specimens of 15.24 cm x 15.24 cm (6 inches x 6 inches) were prepared. The thickness of the specimen was measured and then the specimen was placed on a plastic ring. The specimen was then clamped to the inside of the plastic ring using a metal ring so that there were no obvious wrinkles in the film. To obtain the total haze, the clamped specimen was then placed on the haze port of the sensing unit with the membrane flush with the inlet port, and the haze reading was taken. This process was repeated for all 5 specimens. To obtain the internal haze, a small amount of mineral oil was placed on both surfaces of the membrane and the oil was evenly spread using a cotton swab. The sample was then placed as close to the mist port as possible and the reading was taken. This process was repeated again for all 5 specimens. The surface haze was calculated based on the difference between the total haze and the internal haze.

[0194] pierce

[0195] The standard test method for the anti-protrusion puncture property used in the embodiment is based on ASTM D5748. The above-mentioned puncture test is used to determine the resistance of the film to the probe penetration with a standard low rate, a single test speed. After the film is prepared, the film is conditioned at least 40 hours at 23 ℃ (+ / -2 ℃) and 50%RH (+ / -10%) according to ASTM standards. According to ASTM standards, the standard test conditions are 23 ℃ (+ / -2 ℃) and 50%RH (+ / -10%). Puncture is measured on a tensile tester. From the sheet, a square specimen is cut into a size of about 15.24cm × 15.24cm (6 inches × 6 inches). The specimen is clamped in a circular sample holder of 10.16cm (4 inches) diameter, and the puncture probe is pushed into the center of the clamped film at a crosshead speed of 25.4cm / min (10 inches / minute). The probe used in the examples was a polished steel ball with a diameter of 1.27 cm (0.5 inch) on a support rod with a diameter of 0.635 cm (0.25 inch), which is a slight deviation from the above-mentioned ASTM standard procedure. A single thickness measurement was performed at the center of the sample. For each sample, the maximum force, breaking force, penetration distance, breaking energy, and puncture strength (energy per unit volume of the sample) were determined. A total of 5 samples were tested to determine the average puncture value. The puncture probe was cleaned with a "Kim-wipe" after each sample.

[0196] Dart Impact

[0197] The dart test is used to determine the energy that causes plastic film to fail under specific conditions of free-fall dart impact. The test result is the energy expressed in terms of the weight of the projectile dropped from a specified height that will cause 50% of the specimens tested to fail.

[0198] After film preparation, the films were conditioned at 23°C (+ / -2°C) and 50% RH (+ / -10%) for at least 40 hours according to ASTM standards. According to ASTM standards, standard testing conditions are 23°C (+ / -2°C) and 50% RH (+ / -10%).

[0199] Method A of the test was used, which involved using a dart head with a diameter of 3.81 cm (1.5 inches) and a drop height of 66.04 cm (26 inches). The sample thickness was measured at the center of the sample, and the sample was then clamped by a circular specimen holder with an inner diameter of 12.7 cm (5 inches). The dart was loaded above the center of the sample; the dart was then released by a pneumatic or electromagnetic mechanism.

[0200] Testing of the specimens was performed according to the 'ladder' method. This method provides that if a specimen fails, a new specimen is tested with the weight of the dart reduced by a known and fixed amount; whereas if the specimen does not fail, a new specimen is tested with the weight of the dart increased by a known increment. A total of 20 specimens were tested and the number of failures determined. After testing 20 specimens, if the number of failures was 10, the test was complete; if the number of failures was less than 10, further specimens were continued to be tested until 10 failures were recorded. If the number of failures was greater than 10, further specimens were continued to be tested until the total number of no failures was 10. The dart drop strength was determined from the above data obtained according to ASTM D1709.

[0201] Elmendorf tear

[0202] Elmendorf Tear is measured using the method described in ASTM D1922 Type B (Constant Radius).The Elmendorf Tear Test described above uses an Elmendorf-type tear tester to determine the average force to propagate a tear through a specified length of plastic film or non-rigid sheet material after the tear is initiated.

[0203] After film preparation, the film to be tested is first conditioned at 23°C (+ / -2°C) and 50% RH (+ / -10%) for at least 40 hours according to ASTM standards. According to ASTM standards, standard test conditions are 23°C (+ / -2°C) and 50% RH (+ / -10%).

[0204] The force (in grams) required to propagate a tear on a film or sheet sample is measured using a precisely calibrated pendulum device. Acting by gravity, the pendulum swings in an arc, thereby tearing the sample from the pre-cut slit. One side of the sample is fixed by the pendulum, and the other side of the sample is fixed by a fixed member. The energy loss of the pendulum is indicated by a pointer or an electronic scale. The scale indication is a function of the force required to tear the sample. The sample used is a "constant radius geometry" as specified in D1922. Samples cut from the MD and CD directions are tested. Before testing, the sample thickness is measured at the center of the sample. A total of 15 samples in each direction were tested, and the average tear strength is reported.

[0205] Secant modulus 2%

[0206] Secant modulus 2% is measured using the method described in ASTM D882. The properties of the film are measured when tested under uniaxial extension using the above tensile test. The secant modulus is measured at a specific strain; and the secant modulus is reported as the ratio of the stress at a specific strain to the specific strain, as determined from the load-extension curve.

[0207] After film preparation, the film was first conditioned at 23°C (+ / -2°C) and 50% RH (+ / -10%) for at least 40 hours according to ASTM standards. According to ASTM standards, standard test conditions are 23°C (+ / -2°C) and 50% RH (+ / -10%).

[0208] A 2.54 cm (one inch) wide test strip was cut from the film to be tested and then loaded into a tensile test frame using a line contact fixture with a contact point (gauge length) spacing of 10.16 cm (4 inches). The samples were tested at a crosshead speed of 5.08 cm / min (2 inches / min) to a nominal strain of 5%. The elastic modulus (from the initial portion of the stress-strain curve, commonly referred to as Young's modulus) and the secant modulus at 1% and 2% strain were calculated.

[0209] Shrinkage, shrinkage and compression

[0210] Shrinkage force and shrinkage are measured using the "Retratech" device. In this method, film strips 15 mm wide and 100 mm long are used as specimens, cut in the machine direction (MD) or cross direction (CD). Two specimens are allowed to move freely, and six specimens are restricted from any movement in the test direction (MD or CD). The two freely moving specimens are used to measure the free shrinkage, and the constrained six specimens are used to measure the shrinkage force. When an oven preheated to a selected temperature (set point) is mechanically engaged to initially cover the specimen at ambient temperature, the temperature of the test strip suddenly increases. The specimen physically shrinks, and the amount of shrinkage of the specimen is measured using a displacement sensor connected to one end of the specimen.

[0211] The specimen used to determine the specimen retraction force is connected to a load cell that provides a force signal. These measurements are taken over time as the specimen temperature changes during the test. The temperature profile experienced by the film specimen is a result of the chosen test conditions, which in turn affects the test data.

[0212] There are generally two methods for selecting test conditions (baking temperature set point, holding time, and total time): (1) the method described in ISO 14616; and (2) the fixed condition method. In the above method (1), the test conditions are selected to meet the ISO 14616 requirements for MD specimens. In the above method (2), a fixed set of temperature set points and holding times are set for all samples, and the values ​​of the samples are selected to achieve a well-defined force peak in MD during the temperature rise phase, which eventually relaxes to zero before being removed from the oven. Before the force specimen relaxes to zero force (during the ISO 14616 method), the force will rise as the film specimen cools when it is removed from the oven. The force peak during the temperature rise process is called the "shrinkage force", the maximum shrinkage at the end of the total analysis time is called the "free shrinkage", and the force at the end of the analysis time is called the "shrinkage force".

[0213] result

[0214] Table IV describes the DC numbers of CSF membrane samples tested according to the above-described procedure for measuring DC numbers.

[0215] Table IV - Defect Count Number

[0216]

[0217] Notes to Table IV: *Defect counts (DC) for films are reported as the number of defect counts (DC) per 24.6 cm with effective circle diameters within the specified micrometer range. 3 The number of optical defects.

[0218] **"NP" stands for "Not Processable", i.e., the processability of the r-HDPE samples of the Comparative Examples.

[0219] D was too poor to extrude the film for measuring gel count.

[0220] Table V describes the mechanical properties of the CSF membrane samples tested according to the above procedure.

[0221]

[0222] Table VI describes the optical properties of the CSF film samples tested according to the above procedure.

[0223] Table VI - Optical Properties

[0224]

[0225] Table VII describes the shrinkage properties of the CSF film samples tested according to the above procedure.

[0226] Table VII - Shrinkage Properties

[0227]

[0228] Table VIII describes the processability properties of CSF membrane samples tested according to the above procedure and based on measured head pressure and post-screen pressure.

[0229] Table VIII - Processability Properties

[0230]

[0231] Results and Discussion

[0232] The results described in Tables V-VII show that the collation shrink film (CSF) of Examples 3 and 4 of the present invention has fairly good mechanical properties, which is very important for collation shrink film applications; and when the CSF of Examples 3 and 4 of the present invention is compared with the film of Comparative Example E (without PCR resin), the optical properties of the CSF of Examples 3 and 4 of the present invention using PCR resin are almost at the same level as the optical properties of the film of Comparative Example E.

[0233] The CSFs of inventive examples 3 and 4 show very good shrink properties, even better than the films of comparative examples E and F. Good shrink properties of CSFs are very important properties for finishing shrink film applications. The results described in the above Tables V to VII also show that although the CSFs of inventive examples 3 and 4 combine two different post-consumer recycled (PCR) resin materials and show very good shrink properties, at the same time, the mechanical properties and optical properties of the CSFs of the present invention are not compromised. Therefore, the films of the present invention containing PCR resins are suitable for finishing shrink film applications.

[0234] For example, in a preferred embodiment, the blend formulation of the present invention can be a PCR2 resin (40 / 30 / 30r-LDPE Natural 510A / r-HDPE Natural 921D / LDPE 150) with a 70 wt% PCR resin loading; and the CSF film structure of the present invention prepared from the above blend formulation exhibits good shrinkage performance without compromising the mechanical properties, optical properties and processability properties of the film structure.

[0235] exist Figure 1 In, it is shown that the melt strength of the resin samples of the present invention is higher than that of the resin samples of the comparative examples. For example, the PCR1 resin of Example 1 of the present invention and the PCR2 resin of Example 2 of the present invention surprisingly show an excellent combination of melt strength higher than any constituent component of the resin itself and good stretchability. Stretchability is the maximum speed at which polymer strands break during the melt strength test. A combination of high melt strength and high stretchability is required to ensure good processability and good bubble stability during the blown film manufacturing process. The PCR1 resin of Example 1 of the present invention and the PCR2 resin of Example 2 of the present invention each have a higher melt strength than the resin A of Comparative Example A, the resin C of Comparative Example C, and the resin D of Comparative Example D. In addition, the PCR1 resin of Example 1 of the present invention and the PCR2 resin of Example 2 of the present invention each have a significantly improved stretchability than the resin B of Comparative Example B and the resin D of Comparative Example D.

[0236] Other Implementations

[0237] In one embodiment, the post-consumer recycled resin loading in the core layer of the multi-layer film structure of the present invention is greater than or equal to 70% to 90%.

[0238] In some embodiments, when the entire film structure is a single layer (i.e., no skin layer is present), the post-consumer recycled resin loading in the entire film structure of the present invention is greater than, or equal to, 30% to 90% in one embodiment; and greater than, or equal to, 30% to 80% in another embodiment.

[0239] In some embodiments, when the overall film structure is multi-layer (e.g., a 3-layer or 5-layer film structure), the post-consumer recycled resin loading in the overall film structure of the present invention is greater than, or equal to, 30% to 60% in one embodiment; and greater than, or equal to, 30% to 50% in another embodiment.

[0240] In yet another embodiment, the formulated resins of the present invention further comprise 0.1 wt % to 10 wt % of one or more additives.

[0241] In yet another embodiment, the additives added to the formulated resin of the present invention include one or more additives selected from antioxidants, pigments, colorants, UV stabilizers, UV absorbers, processing aids, fillers, slip agents, anti-blocking agents, compatibilizers, and the like; and mixtures thereof.

Claims

1. A blend resin composition for forming a shrink film therefrom, the blend resin composition comprising: (a) at least one post-consumer recycled resin derived from recycled high density polyethylene resin having a density of 0.940 g / cc to 0.970 g / cc and a melt index I2 of 0.01 g / 10 min to 1.0 g / 10 min; (b) at least one post-consumer recycled resin derived from recycled low density polyethylene resin having a density of 0.915 g / cc to 0.935 g / cc and a melt index I2 of 0.1 g / 10 min to 2.0 g / 10 min; and (c) at least one pristine low density polyethylene resin having a density of 0.915 g / cc to 0.925 g / cc and a melt index I2 of 0.1 g / 10 min to 1 g / 10 min; The resin is formulated with a loading of post-consumer recycled resin of greater than or equal to 30% to 90%.

2. The composition of claim 1, wherein the concentration of the at least one post-consumer recycled resin component (a) of the formulated resin is from 20 wt % to 50 wt %; wherein the concentration of the at least one post-consumer recycled resin component (b) of the formulated resin is from 20 wt % to 70 wt %; and wherein the concentration of the at least one virgin low density polyethylene resin component (c) of the formulated resin is from 10 wt % to 40 wt %.

3. A pelletized article for making a shrink film therefrom, the pelletized article comprising a blend composition, the blend composition comprising: (a) at least one post-consumer recycled resin derived from recycled high density polyethylene resin having a density of 0.940 g / cc to 0.970 g / cc and a melt index I2 of 0.01 g / 10 min to 1.0 g / 10 min; (b) at least one post-consumer recycled resin derived from recycled low density polyethylene resin having a density of 0.915 g / cc to 0.935 g / cc and a melt index I2 of 0.1 g / 10 min to 2.0 g / 10 min; and (c) at least one virgin low density polyethylene resin having a density of 0.915 g / cc to 0.925 g / cc and a melt index I2 of 0.1 g / 10 min to 1 g / 10 min; wherein the loading of the PCR of the formulated resin is greater than or equal to 30% to 90%.

4. The pellet article of claim 3, wherein the concentration of the at least one post-consumer recycled resin component (a) of the formulated resin is from 20 wt% to 50 wt%; wherein the concentration of the at least one post-consumer recycled resin component (b) of the formulated resin is from 20 wt% to 70 wt%; and wherein the concentration of the at least one virgin low density polyethylene resin component (c) of the formulated resin is from 10 wt% to 40 wt%.

5. The pelletized product according to claim 3, wherein: (i) the melt strength of the pellets is greater than or equal to 15 cN; and (ii) a defect count number of the film based on the pellets is such that the number of defects having an equivalent circular diameter in the range of 200 micrometers to 400 micrometers is less than or equal to 20,000 (per 24.6 cubic centimeters of film); And the number of defects with an equivalent circular diameter in the range of 400 micrometers to 800 micrometers is less than or equal to 1,000 (per 24.6 cubic centimeters of film).

6. A shrink film, comprising: At least one monolayer or multilayer film, the at least one monolayer or multilayer film having at least one layer comprising a formulated resin, wherein the formulated resin comprises: (a) at least one recycled high density polyethylene resin having a molecular weight of 0.940 g / cc Density to 0.970 g / cc and melt index to 0.01 g / 10 min to 1.0 g / 10 min I2 post-consumer recycled resin; (b) at least one recycled low density polyethylene resin having a molecular weight of 0.915 g / cc Density to 0.935 g / cc and melt index to 0.1 g / 10 min to 2.0 g / 10 min I2 post-consumer recycled resin; as well as (c) at least one having a density of 0.915 g / cc to 0.925 g / cc and 0.1 g / 10 min to 1g / 10min melt index I2 of the original low-density polyethylene resin; wherein the The loading of post-consumer recycled resin in the formulated resin is greater than or equal to 30% to 90%, while maintaining the initial properties of the shrink film at the same level as that of the film without components The shrinkage films made from the formulated resins of points (a) and (b) have the same level or an improved level.

7. The film of claim 6, wherein the concentration of the at least one post-consumer recycled resin component (a) of the formulated resin is from 20 wt % to 50 wt %; wherein the concentration of the at least one post-consumer recycled resin component (b) of the formulated resin is from 20 wt % to 70 wt %; and wherein the concentration of the at least one virgin low density polyethylene resin component (c) of the formulated resin is from 10 wt % to 40 wt %.

8. The film of claim 6, wherein the film has a thickness of 40 to 100 microns.

9. The film of claim 6, wherein the components (a), (b), and (c) of the formulated resin are first melt blended, and then the resulting melt blend composition is formed into a plurality of pellets.

10. The film of claim 6, wherein the post-consumer recycled resin of component (a) is derived from blow molded plastic bottles.

11. The film of claim 6, wherein the post-consumer recycled resin of component (b) is derived from flexible films.

12. The film of claim 6, wherein the film is a multi-layer collation shrink film having a core layer comprising the formulated resin.

13. The film of claim 6, wherein the film exhibits one or more of the following properties: (i) a haze of less than or equal to 50% when measured according to ASTM D1003; (ii) a puncture resistance of greater than or equal to 3.3 MPa when measured in accordance with ASTM D5748; (iii) a dart impact resistance of greater than or equal to 70 grams when measured in accordance with ASTM D1709 Type A; (iv) an Elmendorf tear strength of greater than or equal to 100 grams-force in the machine direction when measured in accordance with ASTM D1922, Type B (constant radius); (v) a secant modulus 2% greater than or equal to 275 MPa in the machine direction and greater than or equal to 340 MPa in the transverse direction when measured in accordance with ASTM D882; (vi) a shrinkage force in the machine direction greater than or equal to 100 mN when measured according to ISO 14616; (vii) a compression force in the machine direction greater than or equal to 2,600 mN when measured in accordance with ISO 14616; as well as (viii) a free shrinkage in the machine direction of greater than or equal to 65% when measured according to the fixed conditions method described at a temperature set point of 200°C and a dwell time of 50 seconds.

14. The film of claim 6, wherein the formulated resin is in the form of one or more pelletized preparations.

15. A method for manufacturing the shrink film according to claim 4, the method comprising the following steps: (I) melt blending the at least one post-consumer recycled resin component (a), the at least one post-consumer recycled resin component (b), the at least one virgin low density polyethylene resin component (c), and any optional additives to produce the formulated resin; as well as (II) forming at least one monolayer or multilayer film using blown film extrusion, wherein at least one layer of the extruded film comprises the formulated resin.

16. A method of shrink packaging one or more articles or products, the method comprising the steps of: (A) wrapping the one or more articles or products in the heat-shrinkable collation shrink film of claim 1 to form a shrink-wrapped package; as well as (B) heating the shrink-wrap package of step (i) by exposing the wrapped package to sufficient heat to shrink the film, the film thereby pinching the one or more wrapped items and providing intimate contact between the film and the one or more items or articles.

17. A packaged product packaged using a shrink film, the shrink film comprising the shrink film according to claim 6.

18. A collation bag comprising one or more articles and a film to which the one or more articles are bound, the film having been heat shrunk in place by the method of claim 16.

Citation Information

Patent Citations

  • Process for preparation of homogenous random partly crystalline copolymers of ethylene with other alpha-olefins

    US3645992A

  • Ethylene polymer blend and polymerization process for preparation thereof

    US3914342A

  • Hydrocarbon interpolymer compositions

    US4076698A

  • Interpolymers of ethylene and unsaturated carboxylic acids

    US4599392A

  • Elastic substantially linear olefin polymers

    US5272236A